Effect of Discarded Group B and Group D Car Category Tyre Rubber Chippings as Partial Replacement for Coarse Aggregates in M25 Concrete. - Wancha, Vicent (Kabale University, 2023)
After water, concrete is the second most consumed substance worldwide in construction industry. Natural aggregates occupy roughly 65 to 70 percent of the volume in typical concrete. The current research is primarily focused on replacing natural aggregates with sustainable aggregates like (coconut shells, Oil Palm Shells,) and solid wastes like (E-waste, used Rubbers, and recycled Ceramic Tiles) in order to produce good concrete while keeping in mind and to save natural materials for future generations. Utilizing the aforementioned recyclable and commercial waste aggregates can help prevent garbage from being dumped on the ground, reduce groundwater pollution, and lighten concrete by reducing its density. Consequently, my idea concentrated on using old tyres. Concrete of the M25 grade was employed as the reference standard in this experimental study. In this study, the impact of employing scrap tyre rubber as a partial substitute for coarse aggregate (0%, 5%, 10%, and 15% replacement) on various concrete qualities, such as strength and workability, has been noted. Although there was a decrease in strength, it was determined from this experimental study that this type of concrete was suitable for a number of architectural applications requiring medium to low compressive strength. Therefore, the best method of disposal to preserve the environment is to use used tyre rubber to create concrete. It was observed that a mixture of group B and group D scrap tyre rubber chippings in concrete at 15 percent replacement achieved the best result of compressive strength (14.815Mpa) as compared to the control experiment(25.529Mpa) after 56 days of curing unlike group D and group B which showed slightly lower values i.e., 14.232Mpa and 14.661 Mpa respectively.